Ferritin nanocages: A biological platform for drug delivery, imaging and theranostics in cancer. (May 2016) - Truffi, Marta; Fiandra, Luisa; Sorrentino, Luca; Monieri, Matteo; Corsi, Fabio; Mazzucchelli, Serena
Graphical abstract: Abstract: Nowadays cancer represents a prominent challenge in clinics. Main achievements in cancer management would be the development of highly accurate and specific diagnostic tools for early detection of cancer onset, and the generation of smart drug delivery systems for targeted chemotherapy release in cancer cells. In this context, protein-based nanocages hold a tremendous potential as devices for theranostics purposes. In particular, ferritin has emerged as an excellent and promising protein-based nanocage thanks to its unique architecture, surface properties and high biocompatibility. By exploiting natural recognition of the Transferrin Receptor 1, which is overexpressed on tumor cells, ferritin nanocages may ensure a proper drug delivery and release. Moreover, researchers have applied surface functionalities on ferritin cages for further providing active tumor targeting. Encapsulation strategies of non metal-containing drugs within ferritin cages have been explored and successfully performed with encouraging results. Various preclinical studies have demonstrated that nanoformulation within ferritin nanocages significantly improved targeted therapy and accurate imaging of cancer cells. Aims of this review are to describe structure and functions of ferritin nanocages, and to provide an overview about the nanotechnological approaches implemented for applying them to cancer diagnosis and treatment.